Implikasi Penanaman Modal dalam Negeri terhadap Tingkat Pengangguran di Kawasan Pariwisata Candidasa Karangasem - Ni Made Budi Kartika; Desak Gede Dwi Arini; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Currently Indonesia is a country which has a large population, as well as having natural resources (SDA) which is quite abundant, but the community as well as the Government has not been able to take advantage of the natural resources (SDA) in order to increase growth Economics for tackling unemployment in Indonesia, the basic policy of investing that is Act No. 25 of the year 2007, based on the legislation of local government which has the opportunity to attract investors to infuse capital both domestic and foreign, because it has the potential of karangasem geographically such as mountains and beaches become the main purpose of domestic and foreign tourists. The tourism region of candidasa is well worth to optimize as tourism and facilitate economic growth have a direct impact on the reduction of unemployment in Karangasem Regency. As for the formulation of the problem (1) How the shape of the Domestic capital investment in Candidasa Karangasem? (2) How the implications of investing in the country Against the unemployment rate in the area of tourism Candidasa Karangasem? This study uses empirical methods and qualitative data analysis and quantitative, investing in the country's positive effect to the unemployment which exists in the area of tourism candidasa karangasem, local governments have also been promotes training for job seekers at karangsem.